1999
DOI: 10.1259/bjr.72.859.10624321
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to radiocontrast media in an Indian population.

Abstract: This study was conducted to determine the epidemiological characteristics and clinical presentation of adverse reactions to intravenous radiocontrast media (CM) in patients of Indian origin. 379 of 1798 patients who received either sodium iothalamate or sodium meglumine diatrizoate developed adverse reactions (i.e. 21.08% of patients). The incidence of mild, moderate and severe adverse reactions were 19.47%, 1.33% and 0.28%, respectively. One patient who developed a severe reaction expired. There were no diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…15 In contrast to some published reports, we observed no relationship between the incidence of adverse events and the dose of iodine administered. 16 Cochran et al speculated that contrast dose might play a role in the incidence of reactions, because 70% of severe reactions occurred in patients receiving higher iodine doses for computed tomography (CT) angiography. However, Cochran et al were unaware of the exact number of CT examinations performed using a higher contrast dose; therefore, this speculation may be based on a statistical quirk.…”
Section: Discussionmentioning
confidence: 99%
“…15 In contrast to some published reports, we observed no relationship between the incidence of adverse events and the dose of iodine administered. 16 Cochran et al speculated that contrast dose might play a role in the incidence of reactions, because 70% of severe reactions occurred in patients receiving higher iodine doses for computed tomography (CT) angiography. However, Cochran et al were unaware of the exact number of CT examinations performed using a higher contrast dose; therefore, this speculation may be based on a statistical quirk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported no significant difference between genders in RCM hypersensitivity reactions [9, 10, 11]. Interestingly, a recent study conducted in Turkey (1,131 subjects), in Australia (29,962 subjects), and Thailand (55,286 subjects) showed that female gender was one of significant risk factors in RCM-induced hypersensitivity reactions [12] (Table 3).…”
Section: Clinical Manifestations and Risk Factorsmentioning
confidence: 92%
“…Although the prevalence of severe reactions varied depending on the studies, severe life-threatening reactions was 0.04-0.28% [1, 2, 4, 6, 7, 8, 9]. It has also been reported that RCM was the most responsible drug that accounted for 18.0% of in-hospital anaphylaxis in a Korean study conducted in a tertiary hospital [1].…”
Section: Clinical Manifestations and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortele et al 26 observed eight cases (4%) of bronchospasm in a group of 211 patients with adverse events following the use of nonionic iodinated contrast medium for CT and 2.6% of bronchospasm after RCM has been reported in an Indian population 27 . Four (0.38%) asthmatic reactions have been described by Lira et al 28 during fluorescein angiography and, recently, two cases (0.18%) of bronchospasm have been found in children following the use of i.v.…”
Section: Introductionmentioning
confidence: 99%